Agriculture the food we grow and animals we raise - Casper, Julie Kerr. (New York : Chelsea House, 2007)
A comprehensive introduction to U.S. agricultural practices. The chapters cover the history of American farming to sustainable practices for the future. Includes tables, diagrams, a glossary and chronology.
Concepts of agriculture -- History of American farming -- Renewable and nonrenewable resources -- Development of agricultural diversity -- Use of the land and agricultural diversity -- Importance of agriculture -- Management of the land, water, soil and environment -- Conservation of agricultural resources -- Conclusion: Future issues and land stewardship -- Chronology -- Glossary -- Further reading -- Index.
Description based on print version record.
Includes bibliographical references (p. 200-203) and index.
Keywords: Agriculture -- United States -- Juvenile literature; Agriculture; Electronic books; Electronic books